Barriers and facilitators to conducting economic evaluation studies of Gulf Cooperation Council (GCC) countries: a survey of researchers - Saja H. Almazrou; Shiekha S. Alaujan; Sinaa A. Al-Aqeel (BMC, 2021)
Abstract Background The number of published economic evaluations of Gulf Cooperation Council (GCC) countries is notably scarce. Limited local evidence could have a major impact on the implementation of economic evaluation recommendations in the decision-making process in GCC countries. Little is known about the factors affecting researchers who seek to conduct economic evaluations. Therefore, we aimed to assess researcher barriers and facilitators in conducting such studies of GCC countries. Methods A cross-sectional survey of health economic researchers working in GCC countries was conducted online between January and February 2020. The survey instrument collected researchers' perceived barriers and facilitators and demographic information. For barriers, respondents rated their agreement on a 5-point Likert scale ranging from "strongly disagree" to "strongly agree". For facilitators, respondents rated the importance of each facilitator on a six-point scale ranging from "extremely important" to "not very important". Then, participants were asked to select the three most important barriers and facilitators from the lists. The data collected were examined using descriptive analysis. Results Fifty-one researchers completed the survey (37% response rate). The majority of participants (more than 80%) agreed that lack of quality of effectiveness data and restricted access to unit cost data are the main barriers to conducting economic research. Availability of relevant local data was reported as an important facilitator, followed by collaboration between health economic researchers, policy-makers and other stakeholders. Conclusions The results of this study provide an exploratory view of the issues faced by health economics researchers in GCC countries. Recommendations to GCC countries based on international experiences, such as to use real-world data in economic evaluation research, were provided.